Thinking Maps to Promote Critical Thinking through the Teaching of Literature in the ESL Context - Omar, Ainon; Safinas Mohd. Ariff Albakri, Intan (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2016)
The Malaysian education system has emphasized on the importance of producing students as thinking individuals in order to survive in the global era today. The i-Think program which was introduced in schools consists of eight cognitive teaching tools known as thinking maps that teachers can use to mediate students’ thinking, learning, and promote metacognitive behaviours in their lessons. The purpose of this qualitative research study was to determine whether the teachers’ implementation of the Thinking maps promoted critical thinking during the teaching of Literature in the ESL classroom. This case-study was conducted in a secondary school which was one of the pioneer schools selected by the Ministry of Education to implement the thinking maps in the teaching and learning of English language. Data were collected through observations, interviews and field notes. The findings revealed that the teachers were able to engage students to think critically through the use of the thinking maps during their literature lessons. The teachers also employed the Reader-Response strategies to complement the thinking maps in promoting critical thinking in the teaching of literature.